ENCORE: Enhanced Galileo code receiver for surveying applications - Da Silva, Pedro Freire (2011)
In this paper we describe the development of a low-cost high-accuracy Galileo Code receiver, user application software and positioning algorithms for land management applications, which have been implemented using a dedicated FPGA board and dual frequency Galileo E5/L1 Radio Frequency Front-End. The current situation of rural property surveying in Brazil is described and the use of code measurements from the new Galileo signals E5 AltBOC combined with E1 MBOC for use in land management applications is explored. We explain how such approach is expected to allow delivering an absolute positioning solution which could bridge the gap between receivers of high cost/complexity/accuracy based on carrier phase and receivers of lower cost/accuracy based on pseudorange observables. The system is presented together with a detailed description of main components: the Code Receiver and the Application Software. The work presented is part of an ongoing European-Brazilian consortium effort to explore the use of new Galileo for land management applications in Brazil and sponsored by the GNSS Supervisory Authority (GSA).